(3GdZQI GdeNajI aj TQM GdOQI GdCdajIs - (3CHhYHO Gddg TeS GdOjf CMeO Hf GdMSjf Hf CMeO GdEQHdj GdehUdj GHf GdNHGRs; (3GHf eYWj , jMji Hf YHO GdeYWj Hf YHO GdfhQ GdRhGhj, Rjf GdOjf CHh GdMSjf,J (B628 (3g` s ((3YHOGdQMje Hf eMeO Hf YHOGddg Hf gHI Gddg Hf GdefUhQ HGddg s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg Ydi eG CaGV YdjfG aEf YbO GdOQI GdCdajI jYLR Cgd GdYUQ Yf fXe fXjQg s
(3BNQgG (B:s
(3hGMJeGd GdCPi hQDjI LGfjg ZPGA JVhj Hg GdCLSGe LYd Gddg eG JYHJ ajg ef JCdja gPG GdcJGH YedkG aj GdBNQI s
(3GdfSNI ebGHdIs
(3aj GdeYgO fSNJGf CNQjGfs
(3, GfXQ GdLRA GdChd (B117(3, (B118 (3fMhs
(3fSNI KGdKI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdfMhs